DEIXES OF MEMORY IN STENDHAL'S NOVEL 'LE ROUGE ET LE NOIR' - Arwatrisi Ediani; Sajarwa (UIN Raden Mas Said Surakarta, 2022)
Contexts in the identification of referents can be developed from external reality to cognitive reality or memory marked by the French demonstrative determinants ce, cet, cette, and ces as deixes of memory. Information in memory deixis referents can be categorized into the different statuses of information for the hearer, i.e. new information and old information. This study employed the qualitative-descriptive method with the data obtained from the novel Le Rouge et le Noir (1830) written by Stendhal. The study’s findings show that memory deixis referents can be identified through the way they evoke the readers’ old memories or (2) evoke the speakers’ memories and provide new information to the reader. In addition, deixes of memory can be demonstrative and performative. They may be used to describe the social life in 19th century France, to show the speakers’ emotional states, or to introduce a new topic in the text.